Control of element shape and alignment for 3D solution adaptive mesh generation. (February 2020) - Marcum, David; Alauzet, Frédéric
Abstract: A new 3D metric-aligned and metric-orthogonal method for anisotropic tetrahedral mesh generation is presented. The approach uses an advancing-point type point placement that aligns the elements with the underlying metric field and creates quasi-structured local topology. It is based on well-proven methodology and adds novel point-placement strategies that produce solution-adapted anisotropic meshes that are both sized and aligned with the solution gradients upon which the metric field is based. The overall methodology is extended to 3D from a previously developed 2D process. Results for analytical examples and a CFD simulation case are presented that demonstrate that aligned high-quality anisotropic tetrahedral meshes can be reliably generated. Highlights: A new metric-based anisotropic mesh generation procedure is presented for solution adaptation. A new metric-orthogonal/metric-aligned strategy has been developed for advancing-point/advancing-front type point placement. The new approach produces elements that are aligned with the underlying metric field and exhibit pseudo-structured topology. The overall procedure is based on well-proven methodology and adds novel point-placement strategies that produce solution-adapted anisotropic meshes that are both sized and aligned with the solution gradients upon which the metric field is based. Results are presented for multiple examples, including analytical cases and a CFD simulation which, demonstrate that aligned high-quality anisotropic meshes can be reliably generated.